Começar com começar: leituras sobre as configurações de começar em português europeu contemporâneo - Alzamora, Helena; Nunes Correia, Clara (Revista da Associação Portuguesa de Linguística, 2019)
The main objective of this work is the analysis and description of the values of começar in european Portuguese, in order to explain the differences that can be observed in the various configurations in which it occurs, such as < x começar y >, < começar ADV >, < começar Prep INF>, < começar Prep SN>. We try to identify the principles that generate invariance, in spite of the multiple functions these configurations may be associated with. By doing this, we intend to explain the semantic and enunciative properties of this verb in order to describe and explain its different functions. Therefore, it is suggested that the grammatical constructions containing começar can be addressed using a theoretical-methodological support designated by “Schematic Form”. On this hypothesis, see among others Culioli (1990), Paillard (2000), Correia & Coutinho (2006). The “Schematic Form” represents an invariant structure and, at the same time, it shows the deformability originated by the relationship between the verb and its arguments, or among the arguments themselves. We believe that this hypothesis allows for a better understanding of the functioning of the sequences in which this verb occurs.